Pelestarian Lingkungan dan Pemanfaatan Sampah Plastik di Desa Wasuemba Kecamatan Wabula Kabupaten Buton Sulawesi Tenggara - La Gurusi; Samsu Samsu; La Asiri; Junaid Gazalin (Peneliti.net, 2022)
This service aims to encourage community involvement in the process of environmental protection and actions that can be taken by the community to reduce plastic waste pollution. The targets in this service are to build the Plastic Waste Awareness Community Movement, to build a creative community effort by utilizing and managing plastic waste and to become a model as a Waste Awareness Village and a solution to the national plastic waste problem. The location of this community service activity was carried out in Wasuemba Village, Wabula District, Buton Regency.